Volume regulatory responses of basolateral membrane vesicles from Necturus enterocytes: Role of the cytoskeleton - Dubinsky, William P. (The National Academy of Sciences, 1999)
Previous studies from this laboratory have demonstrated that basolateral membrane vesicles isolated from Necturus maculosus small intestinal epithelial cells possess a K(+) channel that is inhibited by ATP. In the present studies, we demonstrate that these vesicles, which are essentially devoid of soluble cytoplasmic contaminants, exhibit volume regulatory responses that parallel those of intact epithelial cells. Thus, suspension of these vesicles in a solution that is hypotonic to the intravesicular solution increases channel activity whereas suspension in a solution that is hypertonic to the intravesicular solution decreases, and may abolish, channel activity. These volume regulatory responses appear to be mediated by the same K(ATP) channel and depend on an intact actin cytoskeletal network. The responses to both hypotonic and hypertonic challenge are abolished by cytochalasin D or by incubating the vesicles under conditions that are known to depolymerize actin. Phalloidin, which is known to stabilize actin filaments, partially prevents the action of cytochalasin D. Thus, the present results indicate that the K(ATP) channel activity of basolateral membrane vesicles from Necturus basolateral membranes respond to hypo- and hypertonic challenge monotonically around an isotonic “set point” and that these responses depend on an intact actin cytoskeleton.